ANALISA SISTEM KENDALI MEKANIK UNTUK PENGEMBANGAN KENDARAAN LISTRIK AUTONOMOUS FAKULTAS TEKNIK UNRAM - I Dewa Ketut Okariawan; Syahrul; Ida Bagus Alit; I Made Nuarsa; I Made Suartika (Jurusan Teknik Mesin dan Industri, Fakultas Teknik, Universitas Mataram, 2023)
Currently, the vehicles that are commonly used are vehicles with fossil fuels, but we all know that these fuels are non-renewable fuels and their availability in nature is very limited, so it is necessary to innovate to use other renewable energy sources. one of which is electrical energy. Besides that, the use of electrical energy for vehicles is currently very relevant because of its relatively high efficiency and friendly to the environment, namely no CO or CO2 gas is formed as in conventional vehicles. Indonesia has the potential to develop electric cars because there is a lot of nickel available to be processed into batteries. Thus, our country has a very large opportunity to produce electric cars. To realize this, it is deemed necessary to conduct a thorough study such as the level of comfort and safety. Thus, it is needed to conduct a study of the mechanical control system so that driving comfort and safety can be achieved. In this research, we will measure the turning radius of the vehicle at various TOE angles. The resulth of this study are the greater of TOE angle produce the higer the turning radius of the vehicle, The smallest turning radius is at a TOE angle 0 degrees which is 4.42 meters and the largest at a TOE angle 1.035 degrees which is 4.53 meters.